Sistem Layanan Ujian Psikotes SIM Menggunakan Computer Based Test Berbasis Website: SIM Psychological Test Service System Using Computer Based Test Based on Website - Suryani Putri, Fadiah; Ngemba, Hajra Rasmita; Hendra, Syaiful; Wirdayanti, Wirdayanti (Technomedia Journal, 2024)
Psychometric tests are a crucial step in obtaining a Driver's License (SIM) that requires effective cooperation between the Traffic Unit (SATLANTAS), psychological institutions, and applicants. However, the psychometric test service often faces challenges due to lack of accuracy and difficulties in manual verification of test results by psychological facilities. To address this challenge, this research develops a web application to facilitate registration, conduct of psychological tests, and access to test results for applicants. This application also assists administrators in managing psychological test information and providing confirmation to applicants. The development process uses the waterfall SDLC method. In its development, testing uses 2 methods: blackbox and the Delone & Mclean method with a qualitative approach involving 47 respondents. Through this research, a SIM psychometric test service system is produced, consisting of account registration, admin and user login, and psychometric test execution pages. The resulting system, named SINAR-SIMPOLRI, can improve the effectiveness and efficiency of psychometric test services in Palu City, providing more efficient support for test participants and psychological facilities in conducting easier checks.